Morphology and mucin histochemistry of the gastrointestinal tracts of three insectivorous mammals : Acomys spinosissimus, Crocidura cyanea and Amblysomus hottentotus - Boonzaier, Julia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MsCMedSc)--Stellenbosch University, 2012.